Floral diversity and forest land-use change towards updating the forest land-use plan of Libagon, Southern Leyte, Philippines - Bacus, Aliah C.
Forest land-use change challenges biodiversity conservation in Libagon, Southern Leyte, where timber poaching and other human activities impacted wildlife habitats and mangrove areas. Despite the 2015 Forest Land-Use Plan (FLUP), local communities continue to struggle with balancing economic needs and sustainable practices, limiting the effectiveness of conservation efforts. This study used a mixed-method approach Flora assessments employed 250-meter transects with 10 m 10 m plots across the cardinal directions (NSEW). Tree species were identified using local knowledge. botanical references, herbarium specimens, and expert validation following IUCN/DENR classifications. Community Knowledge, Attitude, Perception, and Practices (KAPP) data were gathered through surveys of 324 respondents from diverse sectors. Results showed a diverse flora composition in Libagon's forest, with 36 tree species and 22 understory species identified across 21 and 16 botanical families, respectively. Native species dominated the ecosystem, accounting for 95% of trees and 91% of understory vegetation, suggesting strong ecological integrity. Although only about one-third of the forest was surveyed, six tree species were classified as "Vulnerable" and one as "Endangered" under DENR Administrative Order No. 2017-11, including Pterocarpus indicus and Vitex parviflora. Discrepancies between national and international conservation listings emphasized the need for updated site-specific assessments to guide conservation efforts. The Community KAPP survey involved 324 respondents, mostly middle-aged, married, and high school graduated. Despite many identifying as professionals, most lived below the poverty line. Only 107 were aware of the Forest Land-Use Plan (FLUP), indicating limited community familiarity with forest policies, Nevertheless, most respondents recognized trees such as Shorea spp., Pterocarpus indicus, Vitex parviflora, and Artocarpus blancoi as having high importance value, some of which were protected under Presidential Decree No. 705 (Revised Forestry Code of the Philippines). Many supported expanding community participations in FLUP decision-making beyond barangay officials. Respondents aware of FLUP were more likely to perceive increased tree diversity, while the unaware tended to disagree. Although tree planting was common, knowledge gaps in proper reforestation practices persisted. No statistical correlation was found between ecological data and KAPP responses, but community insights generally linked actual forest conditions, supported by a high Shannon Diversity Index (H' = 3.23). The study emphasized the need for enhanced education, law enforcement, and inclusive participation to improve forest management in Libagon.